PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MELALUI METODE BERMAIN MEMBACA SUKU KATA PADA SISWA KELAS I SD INPRES BTN IKIP I KOTA MAKASSAR - Rahma Ashari Hamzah (AIJER: Algazali International Journal Of Educational Research, 2020)
Abstract: Improvement of Beginning Reading Skills Through Syllabary Reading Method For Class I Students of SD Inpres BTN IKIP I Makassar City. This study aims to improve the beginning of reading skills through the method of reading syllables for first grade students of SD Inpres BTN IKIP I Makassar City. This type of research uses a type of classroom action research consisting of two cycles and each cycle consists of four stages namely planning, implementing, observing, and reflecting. The results showed that the application of the syllable reading play method could improve the beginning reading skills, could improve the beginning reading skills of the first grade students of SD Inpres BTN IKIP I Makassar City.